Kegiatan Pendampingan Pembuatan Teh Herbal Bawang Dayak (E.bulbosa), Sungkai (P.canescens) Limpasu (B.lancolata) di GKN, Tanah Bumbu dengan Pendekatan CPOTB - Samsul Hadi; Liling Tryasmono; Deni Setiawan; Gunawan Gunawan; Kunti Nastiti; Noval Noval; Yusri Yusri (Institut Nalanda, 2023)
During the outbreak of SARCOV-2 cases, the search for alternative treatments increased, especially from nature. So that materials from nature get the highest position. In Indonesia, this natural ingredient is known as Jamu. However, use in society is still very simple without any supervision from various security aspects. Therefore, the aim of this activity is to socialize about CPOTB and practice directly the process of making traditional medicine. The methods used in this activity are presentation, discussion, pretest-posttest and practice of making herbal tea. The result of this activity is an increase in the understanding of the community who are members of the GKN prostrations related to CPOTB, this can be seen in the increase in pretest and posttest scores, besides that there is an increase in the ability of GKN members in making traditional medicinal preparations specifically herbal teas, another thing is an increase in ability GKN members in knowing and using traditional medicine making equipment. The conclusion of this activity is that the Kosabangsa activity program carried out in collaboration with UNISM and ULM, has succeeded in making Bawang Dayak, Sungkai and Limsu tea which fulfills the elements of CPOTB.